Intrauterine growth restriction in piglets modulates postnatal immune function and hepatic transcriptional responses independently of energy intake - Amdi, C.; Larsen, C.; Jensen, K. M. R.; Tange, E. Ø.; Sato, H.; Williams, A. R. (Frontiers in Physiology, 2023)
Insufficient prenatal nutrition can affect fetal development and lead to intrauterine growth restriction (IUGR). Large litters in hyperprolific sows have led to an increase in piglets suffering from IUGR. The aim of this study was to investigate hepatic transcriptional responses and innate immune function in piglets suffering from IUGR compared to normal piglets at 3 days of age, and to explore whether provision of an energy rich supplement at birth could modulate these parameters. Sixty-eight piglets were included in the study. Peripheral blood mononuclear cells were harvested for LPS stimulation, and organs harvested post-mortem to quantify relative weights. Liver tissue was utilized for RNAsequencing coupled with gene-set enrichment analysis. IUGR resulted in increased expression of genes such as PDK4, and substantial alterations in transcriptional pathways related to metabolic activity (e.g. citric acid and Krebs cycles), but these changes were not differentequivalent in piglets given an energy rich supplement or not. Transcriptomic analysis and IUGR piglets had changes in transcriptional pathways (e.g. TCA and Krebs cycles) and serum biochemistry indicative ofsuggested impaired altered glucose metabolism and a progressive shift towards oxidation of fatty acids. IUGR piglets also exhibited a suppression of genes related to innate immune function (e.g. CXCL12) and cell proliferationpathways related to cell proliferation (e.g. WNT and PDGF signalling). , Moreover, they produced less IL-1β in response to LPS stimulation, and had lower levels of blood eosinophils, than 2 This is a provisional file, not the final typeset article normal piglets. Taken together, our results indicate that IUGR results in early life alterations in metabolism and immunity that may not be easily restored by provision of exogenous energy supplementation.